Spin pH and SH probes: enhancing functionality of EPR-based techniques. Issue 2 (2004) - Khramtsov Khramtsov, Valery V. Valery V.; Grigor᾽ev Grigor᾽ev, Igor A. Igor A.; Lurie Lurie, David J. David J.; Foster Foster, Margaret A. Margaret A.; Zweier Zweier, Jay L. Jay L.; Kuppusamy Kuppusamy, Periannan Periannan
Abstract : Along with significant progress in low-frequency electron spin resonance (ESR, also called electron paramagnetic resonance, EPR), other techniques such as Longitudinally-Detected ESR (LODESR), proton electron double-resonance imaging (PEDRI) and field-cycled dynamic nuclear polarization (FC-DNP) have been developed for in vivo applications. However their potential is still far from maximally defined, in part, because of the need for new specific function-directed spin probes. An application of stable nitroxides of imidazoline and imidazolidine types provides unique possibility to measure local values of pH and thiol content in various biological systems, including in vivo studies. These applications are based on the observation of specific chemical reactions of these nitroxides with protons or thiols, followed by significant changes in their EPR spectra. To increase sensitivity of pH probes for low-frequency EPR spectroscopy we evaluated two alternative approaches: (i) application of isotopically substituted labels, and (ii) acquisition of EPR spectra at high modulation amplitude. Spatial and spectral-spatial imaging (pH-mapping) using PEDRI and L-band EPR imagers were performed both on phantom samples and in vivo . The applications of the pH and SH probes in model systems, biological fluids, and in vivo in living animals are discussed.